Standards of treatment - modernizationThe gout - Zimmermann-Górska, Irena (Reumatologia/Rheumatology, 2006)
Diagnostic criteria of gout, stages of gouty arthritis, extraarticular manifestations, laboratory diagnostic tests as well as treatment of the disease are presented.